Charcoal data for Lake Masoko, Tanzania - Julie C Aleman; Yannick Garcin; Boris Vannière; Antoine Vullien; David Williamson; C Carcaillet (PANGAEA, 2025)
This dataset contains charcoal concentration data from sediment core samples taken from Lake Masoko, a small volcanic crater lake located in southern Tanzania (9°20.0'S, 33°45.3'E, 840 m a.s.l.), in the Rungwe volcanic region between Mount Rungwe and Lake Malawi. The Masoko composite core spans the entire 50,000-year history of the lake. Several piston-cores were taken in the deepest part of Lake Masoko in 1995 and 1996 (see Gibert et al. (2002) for more details). The core chronology is based on 25 AMS radiocarbon dates of organic matter originally published in Gibert et al. (2002), which have been recalibrated using the latest calibration curve (IntCal20, (Hogg et al., 2020)). This dataset focuses on the last 17,000 calibrated years before present (cal BP), a period for which the median temporal resolution is ~30 years per centimeter. A total of 715 sediment subsamples were collected at 1 cm intervals from the composite core. Each sample (2 cm3 of sediment) was processed using a standard chemical digestion protocol: soaked in 5% KOH, bleached with 10% NaOCl, sieved through a 160 μm mesh, and washed into Petri dishes for area assessments of individual charcoal under a microscope at 40x magnification. These data were produced to reconstruct fire history and to investigate long-term ecological interactions between fire, vegetation, and climate in tropical East Africa during the late Quaternary. The methods follow established sedimentary charcoal analysis protocols (Carcaillet et al., 2001; Whitlock & Millspaugh, 1996).